쌀의 품종에 따른 쌀밥의 감각적 특성 분석 - 김슬기; 윤재연; 하수연; 정광호; 이정희; 정서진; Seulgi Kim; Jae-Yeon Yoon; Suyeon Ha; Kwangho Jung; Chung-Hee Lee; Seo-Jin Chung (Journal of the Korean Society of Food Culture, 2023)
This study aims to analyze the sensory characteristic of cooked rice made with 10 types of rice varieties produced in South Korea using descriptive analysis. Twelve subjects who cook rice regularly, at least once a week, were recruited for the study and participated as descriptive panelists. A total of 29 descriptive terms were developed to describe the sensory characteristics of cooked rice. The findings showed that there were significant differences in the sensory attributes, specifically the appearance and texture attributes among the rice varieties. Among the varieties, Haedeul, Ilpum, and Koshihikari were observed to have a large quantity of rice germ and a relatively yellowish appearance. In contrast, Samkwang, Chamdream, and Yeonghojinmi were relatively whiter than the other samples. Odae, Saecheongmoo, and Sindongjin were rated high in the attributes of roughness, hardness, and chewiness, and Jinsang was rated high in moisture, bitterness, stickiness, and wholeness of rice grains. The differences in the appearance and texture of these rice varieties are likely to significantly impact consumer preferences. Furthermore, the development of customized menus based on the sensory characteristics of the different varieties of rice could encourage consumers to purchase these varieties.